A unique gender difference in early onset melanoma implies that in addition to ultraviolet light exposure other causative factors are important. (21st November 2012) - Liu, Feng; Bessonova, Leona; Taylor, Thomas H.; Ziogas, Argyrios; Meyskens, Frank L.; Anton‐Culver, Hoda
Summary Using US SEER17 Registry data, age‐specific melanoma incidence rates were calculated and comparisons were made between males and females. Relative Risk (RR) for males and females in each age group was computed and compared with that from Nordic Cancer Registry data set and to that for non‐melanoma skin cancer (NMSC). For age groups 44 and younger, females showed higher incidence rates, with a peak difference at age 20–24 (RR = 2.01, 95% CI = 1.21–3.33). Males exhibited higher incidence rates after age 44. The same bimodal gender difference was confirmed by the Nordic Cancer Registry data set, but it was not observed for NMSC, which is known to be strongly associated with cumulative exposure to solar UV radiation. We conclude that exposure to solar ultraviolet (UV) radiation is the major causative factor for melanoma at older age (>44 yr), but that other factors may play a role in early onset melanomas, particularly in females.